How safe are our paediatric emergency departments? Protocol for a national prospective cohort study. Issue 12 (4th December 2014) - Plint, Amy C; Newton, Amanda; Stang, Antonia; Bhatt, Maala; Barrowman, Nick; Calder, Lisa
Abstract : Introduction: Adverse events (AEs), defined as unintended patient harm related to healthcare provided rather than an underlying medical condition, represent a significant threat to patient safety and public health. The emergency department (ED) is a high-risk patient safety setting for many reasons including presentation 'outside of regular hours', high patient volumes, and a chaotic work environment. Children have also been identified as particularly vulnerable to AEs. Despite the identification of the ED as a high-risk setting and the vulnerability of the paediatric population, little research has been conducted regarding paediatric patient safety in the ED. The study objective is to generate an estimate of the risk and type of AEs, as well as their preventability and severity, for children seen in Canadian paediatric EDs. Methods and analysis: This multicentre, prospective cohort study will enrol patients under 18 years of age from nine paediatric EDs across Canada. A stratified cluster random sampling scheme will be used to ensure patients recruited are representative of the overall ED population. A rigorous, standardised two-stage process will be used for AE identification. The primary outcome will be the proportion of children with AEs associated with ED care in the 3 weeks following the ED visit. Secondary outcomes will include the proportion of children with preventable AEs and the types and severity of AEs. We will aim to recruit 5632 patients over 1 year and this will allow us to detect a proportion of patients with an AE of 5% (to within an absolute margin of error of 0.6%). Ethics and dissemination: Ethics approval has been obtained from participating sites. Results will be disseminated through presentations, peer review publications, linkages with emergency research network and a webinars for key knowledge user groups. Trial registration number: This study is registered at Clinicaltrials.gov (NCT02162147 ; https://clinicaltrials.gov/ct2/show/NCT02162147 ).